ANALISIS YURIDIS CROSS REZIM HAK CIPTA DAN DESAIN INDUTRI DI INDONESIA - APRILIANNA SILVIA BERKAT GEA (PREMISE LAW JURNAL, 2016)
Globalization which is identical with free market, free competition, and transparency has great impact on HaKI (Intellectual Property Right) protection in Indonesia. HaKI is a legal instrument which provides protection of the right for a person on his creativity and realization of his intellectual work and gives a right owner to enjoy the economic benefit from his right ownership. Copyright and Industrial Design are a part of HaKI. The case of dispute between Copyright and Industrial Design which has the same legal basis usually occurs in society which is known as cross regime. Protection for copyright is automatic and real expression in realization and without any registration which is given to the copyright holder, while protection for industrial design is not automatic because it is given according to the registration on new design. In the future, it is recommended that respect for the right holders be given, either to copyright holders or to industrial design holders, for their works so that there will be no dispute between them. Keywords: Copyright, Industrial Design, Cross Regime.